Toward holistic corporate sustainability—Developing employees' action competence for sustainability in small and medium-sized enterprises through training - Sophia Schröder; Arnim Wiek; Steffen Farny; Philip Luthardt (Business Strategy and the Environment, 2022)
To advance holistic corporate sustainability in small and medium-sized enterprises (SMEs) requires employees to fully engage in sustainability efforts, which, in return, means to develop employees' action competence for sustainability. Little empirical evidence, however, exists on how to do this considering well-known constraints SMEs face (time, expertise, resources). We present a transdisciplinary project that developed, delivered, and evaluated a sustainability training for the workforce of the Bohlsener Mühle, an SME that has pioneered corporate sustainability in Germany. The training was piloted for the business' apprentices and combined different learning modes to build participants' sustainable action competence. The pre-post evaluation, supported by observations and qualitative interviews, revealed that employees' action competence for sustainability can be fostered through such trainings and is most effective if organizational factors that enable a corporate culture of sustainability are aligned. We conclude that a human-centered and action-oriented approach to training is needed to unleash the full potential of the workforce to advance corporate sustainability.
Keywords: 330; employee engagement; sustainability-oriented workforce; sustainable human resource management; sustainable workforce education; transdisciplinary case study